1964
DOI: 10.1139/f64-004
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Young Atlantic Salmon in a Small Stream

Abstract: The locations of tagged parr and fin-clipped fry were observed from summer through early winter in a 1000-ft (328-m) study area of a small coastal stream. Tagged parr were usually found in or near places of original capture which are herein designated as homes. Parr whose homes were in pools, which appeared to be as suitable habitats as riffles, and those in adjacent riffles appeared to stay in their respective habitats. Some returned to their homes after having been moved as much as 700 ft (213 m) upriver or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
9

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 4 publications
6
80
0
9
Order By: Relevance
“…Cet article expose les résultats obtenus en les comparant à des expériences similaires réalisées en Bretagne sur l'Elorn (Prouzet et al, 1977) et dans d'autres pays (Me Crimmon 1954, Mills 1964, Saunders et Gee 1964, Elson 1975.…”
Section: (2)unclassified
“…Cet article expose les résultats obtenus en les comparant à des expériences similaires réalisées en Bretagne sur l'Elorn (Prouzet et al, 1977) et dans d'autres pays (Me Crimmon 1954, Mills 1964, Saunders et Gee 1964, Elson 1975.…”
Section: (2)unclassified
“…As these parr moved upstream over long distances two or three days after tagging, this behavior probably does not correspond to a post-operative traumatic state. Several studies have established that parr have the capacity to return to their original home sites after being displaced over more than 200 m (Saunders and Gee 1964;Garcia de Leaniz 1989;Huntingford et al 1998), and additional work demonstrated that parr sometimes travelled long distances during hydropeaking (Berland et al 2004;Scruton et al 2003). Considering this important behavioral diversity among our small sample of seven tracked parr, it may be assumed that a large variety of mobility patterns and space utilization exists in Atlantic salmon parr populations.…”
Section: Discussionmentioning
confidence: 79%
“…In comparison to earlier studies using mark-recapture (Saunders and Gee 1964;Hesthagen 1990), visual observation (Steingrimsson and Grant 1999) or passive integrated transponder (PIT) technology Roussel et al 2000Roussel et al , 2004, radiotelemetry permitted locating fish over larger distances under a wider variety of environmental conditions. However, due to the transmitter size limitations, this methodology allows only the study of larger individual parr.…”
Section: Discussionmentioning
confidence: 99%
“…This dispersai, which may be extensive, lasts for a few weeks, but after early dispersion the salmon juvéniles are supposed to be sedentary at least until October (SAUNDERS & GEE, 1969 ;BEALL et al, 1994a). Changes in water conditions often occur during the summer months, usually with a period of low flows in mid to late summer.…”
Section: Introductionmentioning
confidence: 99%
“…LINDROTH (1955) noted that salmonid fry tended to move downstream after a decrease in water flow. SAUNDERS & GEE (1969) observed the movement of parr into the nearest pool during a low flow period, and thieir return to the riffle after flow increase, but this concerned only three individuals, The objective of this study was to assess the movements of parr during or following a severe drop in discharge in semi-natural conditions.…”
Section: Introductionmentioning
confidence: 99%